Development of the Multi-Channel Clustering Hierarchy Method for Increasing Performance in Wireless Sensor Network - Robby Rizky; Zaenal Hakim; Sri Setiyowati; Susilawati susilawati; Ayu Mira Yunita (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2024)
Wireless Sensor Networks are technologies that make it possible to observe phenomena. The problem is data delays in covering the distance from the origin to the destination. Packet Loss is a condition that shows the number of lost packets and the total queue length caused by data processing time. This research aims to develop a cluster-based protocol. This research uses a multichannel hierarchical clustering method and adds odd-even by dividing the network into several channels and forming a cluster head for each channel. The results of this research are Channel 1 with a throughput value of 1.88, channel 2 with a throughput value of 21.68, channel 3 with a throughput value of 1.62, and channel 4 with a throughput value of 42.44. The conclusion of this study is that the throughput results are smaller compared to the Multi-Channel Clustering H ierarchy method, because not all nodes are active